(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2007)
An analysis of botanical researches of bog vegetation of the Southern Bug’s Valley has been presented. There have been distinguished and briefly described the scientific trends, such as floristic, ecological, geobotanical, phytosozological and resources. The urgent issues of the further researches have been considered.